Diffuse dermal angiomatosis mimicking inflammatory breast carcinoma. Issue 2 (26th July 2017) - Hui, Yiang; Elco, Christopher P.; Heinl, Nicole F.; Lourenco, Ana P.; Wiggins, Doreen L.; Wang, Yihong
Abstract: Diffuse dermal angiomatosis (DDA) is a rare pathologically distinct subtype of reactive angioendotheliomatosis. In the literature, few biopsy‐proven cases involving breast skin have been reported. We present a case of a 49‐year‐old female who presented with an indurated, erythematous, weeping, puckered and tender lesion with focal ulceration. Mammography demonstrated diffuse cutaneous and trabecular thickening concerning for inflammatory breast carcinoma. A punch biopsy demonstrated findings consistent with DDA. To our knowledge, this is the first reported case of DDA mimicking inflammatory carcinoma of the breast by clinical and radiologic examination.